2000
DOI: 10.1055/s-2000-8384
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Patterns of Care in Patients with Chronic Obstructive Pulmonary Disease

Abstract: An intimate relationship exists between the physiological processes of respiration and swallowing at all levels of neuromotor control and peripheral function in healthy adults. Little is known regarding the potential alterations in these patterns in patients with chronic obstructive pulmonary disease (COPD), yet the impact of swallowing impairment and aspiration on the health outcomes of patients with COPD may be significant. COPD is a common comorbidity in patients with head and neck cancer and neurological d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…This duration was nearly double that of healthy volunteers, placing patients at increased risk for entrance of liquids and solid food into the airway before the swallow begins and as the swallow continues through full closure of the larynx. Notably, only 1 (9%) of the 11 ARDS patients aspirated the 5-ml thin liquid bolus, suggesting that factors other than timing of swallowing are associated with aspiration in ARDS patients after extubation (e.g., sensation, 47 respiratory-swallow coordination 48,49 ). Although there was no difference in the duration of laryngeal closure, ARDS patients were delayed in re-opening their airway after the swallow.…”
Section: Discussionmentioning
confidence: 99%
“…This duration was nearly double that of healthy volunteers, placing patients at increased risk for entrance of liquids and solid food into the airway before the swallow begins and as the swallow continues through full closure of the larynx. Notably, only 1 (9%) of the 11 ARDS patients aspirated the 5-ml thin liquid bolus, suggesting that factors other than timing of swallowing are associated with aspiration in ARDS patients after extubation (e.g., sensation, 47 respiratory-swallow coordination 48,49 ). Although there was no difference in the duration of laryngeal closure, ARDS patients were delayed in re-opening their airway after the swallow.…”
Section: Discussionmentioning
confidence: 99%
“…Although the body of literature related to symptoms and pathophysiology in PwCOPD with dysphagia is growing, current speechlanguage pathology (SLP) clinical practice patterns in this area are unknown. Similar to dysphagia practice patterns in other populations, [26][27][28] Martin-Harris et al 29 advocated that team-based assessment and management is imperative for the determination of respiratory influence on swallow and ensuring dysphagia did not worsen the respiratory disease. Clinical symptoms in PwCOPD, such as dyspnea, fatigue, anxiety, and hypoxia (reduced oxygen), warrant consideration during the SLP's swallowing assessment and treatment due to the influence these symptoms may have on a PwCOPD's swallowing function.…”
Section: Abstract: Dysphagia Clinical Practice Patterns Chronic Obstructive Pulmonary Disease Swallowing Disorders Respiratory Diseasementioning
confidence: 99%
“…Martin-Harris concluded that patients attempting to maintain breathing activity as long as possible before the obligatory apneic pause, and trying to reestablish respiration quickly while eating semisolids and solids may present channeling of a bolus to the level of the pyriform sinuses and premature opening of the larynx during the latter stages of swallow. [6] The habitual and sometimes necessary mouth-breathing characteristics of COPD patients may lead to excessive dryness and adherence of thick and dry materials to the oropharyngeal tissues, with potential postswallow aspiration.…”
Section: Discussionmentioning
confidence: 99%